Single-cell transcriptomic analysis reveals the association of Ccl6+Ccr2+Arg1+ macrophages with renal interstitial fibrosis in AKI - Xin Zheng; Jiayu Wang; Weinan Chen; Qingquan Xu; Tao Xu; Liang Chen (PLoS ONE, 2025)
Background Acute kidney injury (AKI) is a major health burden with a high risk of progression to chronic kidney disease (CKD). Renal fibrosis is the ultimate outcome of CKD progression, with M2 macrophages playing a critical role by secreting pro-fibrotic factors. Chemokines can influence the progression of renal fibrosis by modulating macrophage polarization during the course of AKI. Methods An integrative analysis of single-cell transcriptomic data from kidneys of mice 7 days after AKI was performed to investigate ligand-receptor (LR) interactions between macrophages and to explore gene co-expression patterns during macrophage differentiation under AKI conditions. The AKI model was induced by unilateral ischemia-reperfusion injury (uIRI), and kidney samples were harvested at day 7. qPCR and WB were employed to measure the transcriptional levels of Ccl6, Ccr2, and M2 polarization markers in macrophages. Transwell assays were performed to evaluate the effect of Ccl6 on BMDMs migration. Cell proliferation was assessed using the Cell Counting Kit-8 (CCK-8) assay. Histological analysis was performed to assess the extent of kidney injury and fibrosis. Multiplex immunofluorescence analysis was conducted to assess the co-localization of Ccl6, Ccr2, and Arg1 expression. Results Through integrated analysis of multiple single-cell transcriptomic datasets from AKI, we identified strong interactions between Ccl6 and Ccr2 in renal macrophages at 7 days post-AKI. Additionally, co-expression of Ccl6, Ccr2, and Arg1 was observed in renal macrophages, and the abundance of Ccl6+Ccr2+Arg1+ cells was positively correlated with the severity of renal interstitial fibrosis. Ccl6 promoted the migration and M2 polarization of bone marrow-derived macrophages (BMDMs). Inhibition of Ccr2 in AKI mice reduced the infiltration of Arg1+ macrophages and attenuated the progression of renal fibrosis. Conclusion Targeting the Ccl6/Ccr2 axis may attenuate fibrotic progression and offers potential therapeutic insights for preventing the transition from AKI to CKD, a possibility that warrants further validation through future functional experiments.